Preventing sports injuries at the national level: time for other nations to follow New Zealand`s remarkable success - Orchard, J. W. (British Journal of Sports Medicine, 2008)
In 2002 Finch and Orchard argued that New Zealand`s socialised approach to preventing sports injuries should, in theory, be superior to the approach of countries like Australia which has a laissez-faire national government approach. This argument was largely based on the fact that such an approach had proved superior for traffic injuries. In 2008 there is evidence to say "case proven"—what works for traffic injuries does work for sports injuries. Researchers working with the New Zealand Accident Compensation Corporation have reported that: With the benefit of a nationwide prevention programme, New Zealand has lowered the incidence rates of catastrophic spinal injuries in rugby union by over 50% for the entire country. The incidence rates in New Zealand are now far lower than the latest reported rates for rugby union in countries such as Australia, South Africa and England. With the benefits of nationwide prevention programmes, the rates of mouthguard usage in contact sports have substantially increased and the rates of dental injuries have substantially decreased. The costs of administering and implementing major nationwide sports injury prevention programmes have been shown in most cases to be far cheaper than the direct and indirect medical costs for the sports injuries prevented